An Alternative Strategy to Adjust the Recombination Mechanism of Organic Photovoltaics by Implementing Ternary Compounds - Gasparini, Nicola; Salvador, Michael Filipe; Fladischer, Stefanie; Katsouras, Athanasios; Avgeropoulos, Apostolos; Spiecker, Erdmann; Chochos, Christos L.; Brabec, Christoph; Ameri, Tayebeh (Advanced Energy Materials, 2015)
Trap-assisted recombination is one of the main loss mechanisms in bulk-heterojunction (BHJ) solar cells. Results suggest that introducing a near infrared (NIR) polymer into the 2,3-bis(3-(octyloxy)phenyl)quinoxaline (PIDTTQ):[6,6]-phenyl C butyric acid methyl ester (PCBM) host system suppresses trap-assisted recombination in the binary blend, leading to a significant improvement of ≈60% in power conversion efficiency for ternary organic solar cells at low light intensity.
Keywords: IR sensitization; low light intensity; organic solar cells; recombination; ternary blends